BEREBUT MASJID: RESISTENSI DAN PENOLAKAN MASYARAKAT ISLAM LOKAL DI ACEH TERHADAP ALIRAN ISLAM PENDATANG: MOSQUE SEIZURE: ISLAMIC RESISTANCE AND DENIAL OF LOCAL COMMUNITIES AGAINST THE MIGRANTS’ ISLAMIC SECTIN ACEH - Marzuki Marzuki (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
Since 2015, there have been some form of rejection (‘public transcript’) against the model of Islamic practice in numerous mosques in Aceh by way of seizing the mosque by a local group of Islamic boarding schools (dayah/ pesantren). What are the local Islamic community claims in response to the newcomer flow in terms of religious belief? What were the reasons underlying seizure of the mosque in Aceh? Those are two questions which will be addressed in this paper. Through interviews and observation, the results show that the local Islamic community, represented by the dayah community have assumed that the new-settler’s religious activities is a cult that is not in line with the established stream of religiositythat has been preserved during the time. Among the underlying causes of the seizure of the mosquein Aceh were; firstly, the mosque is held by the misguided groups. Secondly, the mosque is used as a place for distributing the misguided religious sect. Thirdly, to restore the ordinances of worship in accordance with what is believed by the dayah community in Aceh. Fourthly, the support of the authority, namely the dayah community uses the opportunity from the former leader of the Free Aceh Movement, who is currently the 2017 Governor candidate, promising the establishment of the Ahlussunnah Waljamaah in Aceh. Keywords: Mosques, public transcript, sect of Islam, Aceh. Sejak tahun 2015 telah terjadi beberapa bentuk penolakan (publictranscript) terhadap model pengamalan Islam di beberapa masjid di Aceh dengan cara merebut Masjid oleh golongan Dayah (Pesantren). Bagaimana klaim masyarakat Islam lokal terhadap aliran pendatang? Apa saja sebab yang melandasi perebutan masjid di Aceh? Dua hal ini menjadi pertanyaan yang akan dijawab dalam tulisan ini, melalui wawancara dan observasi. Hasil penelitian menunjukkan, bahwa masyarakat Islam lokal yang diwakili oleh golongan Dayah beranggapan, bahwa aliran pendatang ini merupakan aliran sesat yang tidak sejalan dengan aliran yang dipegang selama ini. Di antara sebab yang melandasi terjadinya perebutan masjid adalah: Pertama, masjid tersebut dipegang oleh golongan yang diklaim sesat. Kedua, masjid telah dijadikan sebagai tempat penyebaran aliran yang diklaim sesat tersebut. Ketiga, mengembalikan tata cara ibadah sesuai dengan yang diyakini oleh golongan Dayah di Aceh. Keempat, adanya dukungan penguasa, yaitu menggunakan kesempatan atau peluang bagi golongan Dayah, karena salah satu petinggi dari mantan Gerakan Aceh Merdeka adalah Calon Gubernur tahun 2017 yang menjanjikan tegaknya ajaran Ahlussunnah waljamaah di Aceh apabila dia terpilih. Kata Kunci: Masjid, public transcript, aliran Islam, Aceh.